2000
DOI: 10.1177/10454411000110020201
|View full text |Cite
|
Sign up to set email alerts
|

Oro-Facial Gangrene (Noma/Cancrum Oris): Pathogenetic Mechanisms

Abstract: Cancrum oris (Noma) is a devastating infectious disease which destroys the soft and hard tissues of the oral and para-oral structures. The dehumanizing oro-facial gangrenous lesion affects predominantly children ages 2 to 16 years, particularly in sub-Saharan Africa, where the estimated frequency in some communities varies from I to 7 cases per 1000 population. The risk factors are poverty, malnutrition, poor oral hygiene, residential proximity to livestock in unsanitary environments, and infectious diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 106 publications
4
99
0
8
Order By: Relevance
“…[3] Fusobacterium necrophorum and Prevotella intermedia are the suspected causative organisms. [2] [3], [8] Children at risk for Noma have been seen to have low plasma concentrations of zinc, retinol, ascorbate, and essential amino acids with increased plasma and saliva levels of free cortisol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Fusobacterium necrophorum and Prevotella intermedia are the suspected causative organisms. [2] [3], [8] Children at risk for Noma have been seen to have low plasma concentrations of zinc, retinol, ascorbate, and essential amino acids with increased plasma and saliva levels of free cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…[3], [6] The risk factors for Noma include poverty, malnutrition, immunosuppression (including HIV infection), poor oral hygiene, unsanitary environment, leukemia, and infectious diseases caused by measles and herpesviridae. [2], [3],[6], [7] It is usually seen in children between the ages of 3 and 12 years mainly in the developing countries especially sub-Saharan Africa. [3], [6] WHO (1998) estimated a worldwide incidence of 1 40 000 cases per year with prevalence of 7 70 000 people living with Noma sequelae (in 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many surveys in different part of the world have found brushing to be the best way to maintain oral health [15] . Enwonwu in 2000, found that poor oral hygiene is one of the main cause of Noma [16] . The study showed that the frequency of the tooth brushing of the respondent increased, the severity of dental plaque decreased, but this relation was not statistically significant (p>0.05) ( Table-3).…”
Section: Dental Plaque Indexmentioning
confidence: 99%
“…Also referred to as "cancrum oris‖ is described as a "gangrenous affection of the mouth, especially attacking children in whom the constitution is altered by bad hygiene and serious illness, especially from the eruptive fevers, beginning as an ulcer of the mucous membrane with edema of the face, extending from within out, rapidly destroying the soft parts and the bone, and almost always quickly fatal.‖ [24] The mucous membrane becomes inflamed and develops an ulcer. The infection then spreads to the skin causing necrosis of the lips and cheeks.…”
Section: Nomamentioning
confidence: 99%